Character-Based Strategic Planning Model for Student Development in SMA Kolese Loyola Semarang - Ajie, Gregorius Rohastono; Puji Sugiharto, Dwi Yuwono; Soesanto, Soesanto; Rusdarti, Rusdarti (Universitas Negeri Semarang, 2018)
Education at SMA Kolese Loyola (Loyola College High School) Semarang implements student coaching based on honest character, discipline, independence, hard work, and responsibilities that are in accordance with the school's vision. This study uses a qualitative approach with a case study design; the process is through data collection using observation and interview techniques. The focus of the research conducted in SMA Kolese Loyola Semarang were (1) finding character-based student development strategic planning; (2) analyzing the implementation of student coaching based on honest, discipline, independent, hard work, and responsibility characters, (3) analyzing the control of the implementation of character-based student coaching. This study found that SMA Kolese Loyola Semarang (1) carried out strategic planning for character-based student development; (2) face obstacles in strategic planning from inside and outside the school. Barriers from within the school are faced through agreements with parents of students, barriers from outside the school are faced through adjusting the implementation of strategic plans for character-based student development in schools; (3) controlling character-based student development activities. The conclusions of the study were that the character-based student planning strategic planning at SMA Kolese Loyola Semarang was a combination of reflection-action experience; interactions between students in school form a person who is characterized by honesty, discipline, independence, hard work, and responsibility.